CHARACTERISTICS OF NORTH JAVA FISHERMAN WITH VESSEL - Maulana Firdaus; Riesti Triyanti (Faculty of Fisheries and Marine Science, Brawijaya University, 2017)
This study aims to determine the characteristics of the fishing vessel < 5 GT restricted to household characteristics and fishing bussines activity. Indramayu regency chosen as the location for a center for fisheries research on the northern coast of Java. Types of data collected in this study are primary and secondary data. The data collection is done by three techniques, namely direct interviews, recording data related to the study of institutions and observation. The number of fishermen who seek respondents as many as 49 people from different households. Respondents were selected by purposive sampling in accordance with the objectives. The data collected is then analyzed descriptively. Financial analysis approach used to calculate the reception and the costs associated with production. The results showed that the age of most of the fishermen belonging to the group of young household members (productive age) with the level of education in mayority is the equivalent of primary school. Most number of household members as much as 3-5 people. Total investment value of the fishing unit about Rp. 43.360.000,-. Total costs incurred by fishermen during the year about Rp. 112 560 000, -. The revenue during the year about Rp.247.239.000, - with the average profits about Rp. 11.223.250,-/ month.